Natural weathering and hygrothermal aging studies of jute/glass fibres reinforced unsaturated polyester hybrid Composites. - Tay, Hong Kang (2011)
Kajian terhadap ketahanan komposit polyester tak tepu (UP) mengandungi dua bahagian. Bahagian pertama adalah untuk menyiasat pengaruh pencuacaan semulajadi terhadap sifat-sifat mekanikal dan morfologi matrik UP dan komposit-komposit diperkuat gentian jut (JF), gentian kaca (GF) dan gentian hibrid jut/kaca (JF/GF). . The research on the durability studies of unsaturated polyester (UP) based composites consists of two parts. The first part is mainly to investigate the effects of natural weathering on the mechanical and morphological properties of UP matrix as well as jute fibre- (JF), glass fibre- (GF) and jute/glass hybrid (JF/GF) fibrereinforced UP composites were investigated.